Rectal prolapse in systemic sclerosis: a rare but demanding surgical scenario - Suárez-Mondragón, Ana K.; Dámazo-Escobedo, Cristian A.; Baigts-Arriola, Luis A.; López-Borel, Alfonso (International Journal of Research in Medical Sciences, 2025)
Rectal prolapse is a relatively common gastrointestinal manifestation in patients with systemic sclerosis. However, its surgical repair in this group of patients requires special consideration due to its association with a high rate of failure and recurrence. We present the case of a 57-year-old woman with systemic sclerosis and grade V Oxford rectal prolapse, successfully resolved through laparoscopic ventral rectopexy. There was follow up for two years with no evidence of recurrence. There are few documented cases of surgical repair in patients with systemic sclerosis, and this is the first reported case of successful repair using this surgical technique. Given the above, the documentation of this case provides a valuable reference for physicians encountering this rare condition associated with a high recurrence rate.